Upaya Guru Kelas Dalam Meningkatkan Minat Belajar IPS Pada Siswa Kelas Tinggi Di SD Negeri Lamtheun Aceh Besar - Rahfiandi Purba; M. Husin; Nurmasyitah Nurmasyitah (Universitas Syiah Kuala, 2023)
The teacher's effort is an activity that must be carried out by a teacher in guiding, honing abilities, and shaping the character potential of students. In the teacher's effort, there is a problem experienced by class teachers in increasing interest in social studies learning, namely how the class teacher implements in increasing interest in social studies learning in high grade students. In addition to efforts, what are the obstacles experienced by classroom teachers in increasing interest in learning social studies in high-grade students? Therefore, researchers want to conduct research at SD Negeri Lamtheun to find out about the efforts of classroom teachers in increasing interest in learning social studies in high-grade students and to find out what obstacles are experienced by teachers who are carried out at SD Negeri Lamtheun Aceh Besar which is the goal of the problem in this research. By using a qualitative approach in a descriptive way. Sources of information were obtained from teachers in grades IV V through observations and interviews about how educators increase students' interest in social studies learning in their classrooms. Based on the results of observational data analysis, the teacher applies learning methods that can develop an increasing interest in learning social studies in high school as a whole, and run well. While the results of the interview with Mrs. Aniyat Mrs. Rasyhida got good results in increasing interest in learning social studies, it's just that there must be follow-up in adding learning media and teaching materials from schools in order to achieve the goals of the vision mission. Therefore, good communication must be established between teachers and schools in order to achieve better learning goals and achieve goals in increasing student interest in learning.